STUDENTS' MATHEMATICAL CRITICAL THINKING ABILITY REVIEWED FROM EXTROVERTED AND INTROVERTED PERSONALITY TYPES - Herlina Hidayati; Riyandy Riyandy (STKIP MUHAMMADIYAH SAMPIT, 2022)
This study aimed to describe the mathematical critical thinking skills of eighth grade students of SMPN Satap 2 Mentaya Hulu through story questions reviewed from extrovert and introvert personality types. This study used a qualitative approach. The subjects in this study were four students who were grouped into two students with an extroverted personality type and two students with an introverted personality type. The method used in this research was test and interview method. The results of this study indicated that in the identify and define indicators, extroverted students were unable to explain the main idea of the problem and were unable to mention what was known and asked in the question, while introverted students are able to explain the main idea of the problem and were able to mention what is known and asked in the question. In the enumerate and list indicators, extroverted students have not been able to mention other options for solving problems and are not able to provide good explanations, while introverted students were able to mention other options for solving problems and were able to provide good explanations. In the analyze indicator, extroverted and introverted students were good at explaining. In the self-correct indicator, extroverted students have not been able to correct answers thoroughly, while introverted students were able to correct answers as a whole.